Analisis Shopping Lifestyle dan Digital Marketing Produk Ramah Lingkungan pada Kalangan Perempuan Lintas Generasi - Rahardani, Margareta Ernanda; Jati, Agustinus Kismet Nugroho (JEMAP, 2024)
This research was conducted to find out how each generation (X, Y, Z) of women differs in responding to the shopping lifestyle which influences the choice of environmentally friendly products and the role of digital marketing in promoting these products so that women choose environmentally friendly products for consumption. This descriptive quantitative research was conducted using a purposive sampling method on 150 respondents by distributing online questionnaires. The results of research on shopping lifestyle showed that women from generation Z had a higher sensitivity to environmentally friendly products with very good points of 218.56. Meanwhile, the role of digital marketing in promoting environmentally friendly products has positive feedback for women from generation Z with a total of 217.4 points.